Step
*
1
of Lemma
triangular-reciprocal-series-sum
.....assertion..... 
lim n→∞.r(2) - (r(2)/r(n + 2)) = r(2)
BY
{ Assert ⌜lim n→∞.r(2) - (r(2)/r(n + 2)) = r(2) - r0⌝⋅ }
1
.....assertion..... 
lim n→∞.r(2) - (r(2)/r(n + 2)) = r(2) - r0
2
1. lim n→∞.r(2) - (r(2)/r(n + 2)) = r(2) - r0
⊢ lim n→∞.r(2) - (r(2)/r(n + 2)) = r(2)
Latex:
Latex:
.....assertion..... 
lim  n\mrightarrow{}\minfty{}.r(2)  -  (r(2)/r(n  +  2))  =  r(2)
By
Latex:
Assert  \mkleeneopen{}lim  n\mrightarrow{}\minfty{}.r(2)  -  (r(2)/r(n  +  2))  =  r(2)  -  r0\mkleeneclose{}\mcdot{}
Home
Index